The hip adductor muscle group in caviomorph rodents: anatomy and homology - García Esponda, César M. (2015)
Anatomical comparative studies including myological data of caviomorph rodents are relatively scarce, and have resulted in the lack of use of muscular features in cladistic and morphofunctional analyses. In rodents, the hip adductor muscles constitute an important group of the hindlimb musculature, having and important function during the fbeginning of the stance phase of locomotion. These muscles are subdivided in several disctinct ways in the different clades of rodents, making the identification of their homologies hard to establish. In this contribution we provide a detailed description of the anatomical variation of the hip adductor muscle group of different genera of caviomorphs rodents, and identify the homologies of these muscles in the context of the Rodentia. On this basis, we recognize the characteristic pattern of the hip adductor muscles in Caviomorpha. Our results indicate that caviomorphs present a singular pattern of the hip adductor musculature that distinguishes them from other groups of rodents. They are characterized by having a single m. adductor brevis that includes solely its genicular part. This muscle, together with the m. gracilis, composes a muscular sheet that is medial to all other muscles of the hip adductor group. Both muscles probably have a synergistic action during locomotion, where the m. adductor brevis reinforces the multiple functions of the m. gracilis in caviomorphs. Mapping of analyzed myological characters in the context of Rodentia indicates that several features are recovered as potential synapomorphies of caviomorphs. Thus, analysis of the myological data described here adds to the current knowledge of caviomorph rodents from anatomical and functional points of view, indicating that this group have features that clearly differentiates them from other rodents.